2012
DOI: 10.1007/s10278-012-9538-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Visually Lossless Compression Ratio Determination of JPEG2000 in Digitized Mammograms

Abstract: The current study presents a quantitative approach towards visually lossless compression ratio (CR) threshold determination of JPEG2000 in digitized mammograms. This is achieved by identifying quantitative image quality metrics that reflect radiologists' visual perception in distinguishing between original and wavelet-compressed mammographic regions of interest containing microcalcification clusters (MCs) and normal parenchyma, originating from 68 images from the Digital Database for Screening Mammography. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Given these results, it is interesting to note that the SSIM threshold used in [BXH∗17] was chosen as 0.98 based on suggestions from the medical literature (e.g, [GKS∗12a], [Weg10]). Using a SSIM threshold of 0.98, the estimated proportion different for this threshold value is 0.9588 (0.9740, 0.9354), where the values in parenthesis provide the 95% confidence bounds for the estimate.…”
Section: Analysis Of Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Given these results, it is interesting to note that the SSIM threshold used in [BXH∗17] was chosen as 0.98 based on suggestions from the medical literature (e.g, [GKS∗12a], [Weg10]). Using a SSIM threshold of 0.98, the estimated proportion different for this threshold value is 0.9588 (0.9740, 0.9354), where the values in parenthesis provide the 95% confidence bounds for the estimate.…”
Section: Analysis Of Survey Datamentioning
confidence: 99%
“…The authors in [BXH∗17] indicate that the SSIM threshold chosen was largely inspired by suggestions from the medical imaging field, where lossy compression is typically used to reduce unmanageable data volumes (e.g., [CP16, KR12, Wan11, KS06]). Indeed, the loss of critical information (a concern shared by climate scientists) is understandably a concern with procedures such as computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound imaging (e.g., [KBMG13, KMLH10, GKS∗12b]). However, an acceptable SSIM threshold varies by application, and the authors in [BXH∗ 17] acknowledge that further research is required to confidently select one for CESM images.…”
Section: Introductionmentioning
confidence: 99%
“…The constant values are of particular interest when applying directly to floating-point simulation data, as discussed in the next section. Another implementation detail is the local window (or patch) for which the per-pixel SSIM value statistics (mean, variance and covariance) are computed in (8). The recommendation in [1] is an 11 × 11 window with a Gaussian filter kernel.…”
Section: B Implementationmentioning
confidence: 99%
“…For example, in the medical imaging field, images are typically compressed to reduce unmanageable data volumes, but clearly the potential loss of critical information (i.e., details needed to make an accurate diagnosis) is a concern. The SSIM has been advocated as a means of evaluating compressed-medicalimage quality in many studies (e.g., see [8]- [12]).…”
Section: Introductionmentioning
confidence: 99%
“…These databases are important tools used to evaluate the performance of image quality assessment (IQA) metrics in the context of streamed videos or pictures displayed on web pages, but their results may not translate well to text images, graphics or diagnostic images. Some studies involving diagnostic images and trained radiologist have shown SSIM to be either on par [6,7] with or better [8] than MSE, but they have not explored its limitations.…”
Section: Previous Workmentioning
confidence: 99%